Relation of red cell distribution width with dipper and non-dipper hypertension - Eyup Buyukkaya; Ali Erayman; Esra Karakas; Alper Bugra Nacar; Mustafa Kurt; Sule Buyukkaya; Adnan Burak Akcay; Nihat Sen (Medicinski glasnik, 2016)
Aim: Red cell distribution width (RDW), an index of erythrocyte size, is associated with high risk for cardiovascular disease. Nondipping hypertension (HT) is lack of nocturnal fall in blood pressure (BP). The association between RDW and non-dipping BP in normotensive and hypertensive patients was investigated. Methods: A total of 170 patients were categorized into 4 groups: Normotensive-Dipper (NT-D), Normotensive-Non-dipper (NTND), Hypertensive-Dipper (HT-D) and Hypertensive-Non-dipper (HT-ND). RDW and hs-CRP levels were measured. Results: Hypertensive patients had higher RDW and hs-CRP levels (14.5 ± 0.87 vs.12.7 ± 0.66, p<0.001 for RDW; 0.99 ± 0.52 vs.0.63 ± 0.43, p<0.001 for hs-CRP). Besides, the RDW levels were higher in non-dippers (13.0 ± 0.63 vs.12.4 ± 0.55, p<0.001 for NT-ND and NT-D; 14.9 ± 0.78 vs.14.2 ± 0.82, p<0.001 for HT-ND and HT-D) Conclusion: RDW is elevated in non-dipping BP both in normotensive and hypertensive subjects, which may be related with increased inflammatory state.
Keywords: blood pressure; circadian rhythm; erythrocyte size; inflammation